Shifting towards sustainability? Questioning the effectiveness of policymaking for intermodal freight transport. (24th November 2022) - Witte, Patrick; Wiegmans, Bart; Jong, Tom De; Oort, Frank Van
Stimulating combined and Intermodal Freight Transport (IFT) to foster sustainability has been on the global policy agendas for a long time. An understudied dimension in this debate is the effectiveness and efficiency of IFT policies. This paper presents an academic literature review of goals, indicators and methods of IFT policies. An ex-post evaluation of the 2001 and 2011 EU white papers on freight transport shows that from a policy dimension, attention to modal shift, sustainability and capacity is visible, but that ambitious goals are oftentimes not supported by concrete targets and realistic budgets. Our proposed alternative, a GIS data-based exploration of the dense IFT network in the Netherlands shows that many industrial or logistics companies are already located at strategic locations with multi-modal accessibility. That despite this precondition the market share of combined and intermodal freight transport is still so small, seriously questions the effectiveness of 30 years of policy attention to IFT.